2007
DOI: 10.1111/j.1399-6576.2007.01376.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3 g of intravenous paracetamol on post‐operative analgesia, platelet function and liver enzymes in patients undergoing tonsillectomy under local anaesthesia

Abstract: During the initial hours after tonsillectomy, the administration of 3 g of i.v. paracetamol and 75 mg of diclofenac reduced the consumption of morphine. Both drugs also reduced the release of thromboxane B(2) from activated platelets but only diclofenac had a negative effect on platelet aggregation. In sensitive individuals, large doses of paracetamol may disturb the hepatocellular integrity. We do not recommend the use of i.v. doses of paracetamol higher than 1 g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…GSH is the substrate of an enzymatic reaction catalyzed by GSTA1 (28); therefore, GSTA1 may theoretically reflect the degree of liver damage. In the APAP model, the protein content and mRNA expression of GSTA1 significantly decreased in accordance with previous predictions that GSTA1 is affected byAPAP-induced hepatic injury (29). The significant decrease of GSTA1 suggests that it maybe released as an antioxidant to protect the liver from various hepatotoxins.…”
Section: Discussionsupporting
confidence: 69%
“…GSH is the substrate of an enzymatic reaction catalyzed by GSTA1 (28); therefore, GSTA1 may theoretically reflect the degree of liver damage. In the APAP model, the protein content and mRNA expression of GSTA1 significantly decreased in accordance with previous predictions that GSTA1 is affected byAPAP-induced hepatic injury (29). The significant decrease of GSTA1 suggests that it maybe released as an antioxidant to protect the liver from various hepatotoxins.…”
Section: Discussionsupporting
confidence: 69%
“…However, there are insufficient data for the use of intravenous paracetamol in migraine attacks. Intravenous acetaminophen differs from the available intravenous opioids and NSAIDs as it is not associated with the adverse effects (nausea and vomiting, and respiratory depression) seen after opioid use, or with platelet dysfunction, gastritis and renal toxicity that are related to NSAID use 8 9. Intravenous acetaminophen is rarely associated with hepatotoxicity, and has been shown to be safe even with underlying liver conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the production of parenteral forms of non-steroidal anti-inflammatory drugs (NSAIDs), the analgesic efficacy of these drugs has become a topic of interest to researchers. In particular, an intravenous form of paracetamol has been introduced and, compared with other NSAIDs, is an effective drug in various types of pain7 8 with a wide safety margin and a low incidence of side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Five randomized, placebo‐controlled trials were identified; all compared intravenous acetaminophen with placebo . The benefit of intravenous acetaminophen over its comparator in pain control and opioid consumption was not consistent across the studies.…”
Section: Clinical Trialsmentioning
confidence: 99%